Hypolipidemic Effect of Apigenin Extracted From Parsley (Petroselinum sativum L.) Leaves In Cadmium Chloride Treated Rats (Part II) - Khudiar, Khalisa Khadhim; Almzaien, Aous Kahtan Ahmad; Almzaien, Kahtan Ahmad (Journal of Kerbala for Agricultural Sciences, 2019)
Cadmium has been reported to have cumulative effects on mortality ,cardiovascular , renal and neurologic .flavonoids (apigenin) are naturally occurring phytochemicals possessed divers pharmacological effects hypolipidemic and antioxidant activity .this study was carried out to investigate the protective effect of the flavonoids extracted from (Petroselinum sativum) parsley leaves on some parameters related to cardiac risk in adult male rats exposed to 50 ppb cadmium chloride in drinking water . Crude flavonoids were extracted from parsley leaves . Further purification of flavonoids was performed by gel permeation column chromatography (TLC) . Thirty adult Albino male rats randomly and equally divided into three group (10 rats for each) and were treated daily for 60 days as follows : The rats were kept on ordinary tab water as control (group c) , received drinking water containing 50 ppb of cadmium chloride (group T1) and simultaneously given orally 150mg/kg B.W. of flavonoids (apigenin) extracted from parsley in addition to 50ppb of cadmium chloride in drinking water (group T2). Fasting blood sample were collected by cardiac puncture technique at 0,30 and 60 days of experiment for measuring the flowing parameters : serum lipid profile including: a. triacylglycerol (TAG) .b. serum total cholesterol (TC) .c. serum high density lipoprotein (HDL-C). d. serum low density lipoprotein (LDL-C).e. serum very low density lipoprotein (VLDL-C) concentration .Besides section from heart, aorta were taken at the end of experiment for histopathological study .The results showed that the yield of crude flavonoids from parsley leaves were approximately 2.68% of dray leaves .Purification of crude flavonoids on Sephadex LH-20 clarified three peaks activity and the proportions of the purified fraction P1, P2 and P3 were 14.06, 82.43 and 3.5% respectively. Thin layer chromatography confirmed that p2 was pure apigenin . the result revealed that animal exposed to 50 ppb of cdcl2 water for 60 days caused cardiac damage manifested by a significant elevation in serum TC,TAG,HDL-C,VLDL-C and LDL-C concentrations, with a significant depression in serum HDL-C concentration . Gavage of flavonoids and Cd concurrently caused a significant correction of the previous studies parameters . Histological section of the heart and aorta of cd treated (T1) group revealed an occurrence of early signs of atherosclerotic lesions . Such histological change could not be observed in heart and aorta of animal in group T2 after oral intubation of flavonoids (apigenin). It could be concluded that apigenin is effective in prevention the deleterious effect of cadmium chloride on major rick factors of cardiovascular system.